Audit Mutu Hukum Pengaturan dan Penerapan Pertanggungjawaban Sosial Bank Melalui Program One Village One Company (OVOC) terhadap Badan Usaha Milik Desa (BUMDes) di Jawa Barat - Tri Putri Natalia (Wajah Hukum, 2020)
West Java Provincial Government seeks to help the independence of the village in order to improve the economy of rural communities by launching the OVOC program. The legal basis for the OVOC program is summarized in a joint agreement formed between the West Java Provincial Government and the BJB Bank. This writing will examine the responsibilities of the West Java Provincial Government as a stakeholder in the implementation of the OVOC program. The next legal issue is the social responsibility of banking institutions through the OVOC program in terms of the mutual agreement that has been formed. There are some gaps between the contents of the joint agreement with the reality that is happening on the ground, one of which is funds that are still stalled in the West Java Provincial Government for BUMDes in West Java. The results of this paper indicate that a legal quality audit of a joint agreement regarding the OVOC program must be carried out bearing in mind there are 7 (seven) quality criteria that must be considered for the interests of the parties involved in it. In its relationship with banking institutions, banking institutions should contribute to the implementation of capacity building, technical assistance, and utilization of banking service facilities as a form of social responsibility for the OVOC program.